The effectiveness of e-tutoring in an open and distance e-learning environment: evidence from the university of south africa. (4th May 2021) - Maré, Suné; Mutezo, Ashley Teedzwi
ABSTRACT: Unisa has embraced the use of online learning and e-tutoring as a new approach to teaching and learning in an ODeL environment. According to the Community of Inquiry Theory, a learning community is important to enhance the social, cognitive and teaching presences for online learning to achieve student success. Online e-tutor and student interaction could provide a learning community environment that reduces the feeling of isolation and may improve student performance at an ODeL institution. The aim of the study is to determine the effectiveness of e-tutoring with regard to student performance in the Department of Finance, Risk Management and Banking in order to enhance student success. Two groups of students were tested; those who participated on e-tutor sites and those who did not and data for five modules were collected. Examination scores of participating and non-participating students were statistically tested to determine whether there were significant differences in performance between the two groups. The results indicated that students who engaged on e-tutor sites had performed better than those who did not, which affirmed the effectiveness of e-tutoring as a student support programme in the Department. The results should assist other ODeL universities to enhance student support through active e-tutoring.